2021
DOI: 10.3390/polym13142370
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Anthelmintic Mechanisms of Action of a Synthetic Peptide: An Ultrastructural and Nanomechanical Approach

Abstract: Resistant nematodes are not affected by the most common drugs commercially available. In the search for new anthelmintics, peptides have been investigated. Here, a linear synthetic peptide named RcAlb-PepIII bioinspired from the antimicrobial protein Rc-2S-Alb was designed, synthesized, and tested against barber pole worm Haemonchus contortus. The physicochemical properties of the peptide, the 3D structure model, the egg hatch inhibition, and larval development inhibition of H. contortus were carried out. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Pimentel-Acosta et al [ 16 ] also reported that silver nanoparticles at high and low concentrations activated dysregulation of similar biological processes (detoxification, neurotoxicity, modulation of cell signaling, embryonic development, reproduction, and tegument organization) by different mechanisms in metazoan parasites of fish. Since cuticle can act as a diffusion barrier for various anthelmintic compounds [ 17 ], combination of silver with conventional anthelmintic agents may allow better penetration of worm body. Silver nano-particles were shown to pass cell membranes and getting internalized in C. elegans by Meyer et al [ 18 ], and they proposed part of the toxicity observed to be mediated by ionic silver.…”
Section: Resultsmentioning
confidence: 99%
“…Pimentel-Acosta et al [ 16 ] also reported that silver nanoparticles at high and low concentrations activated dysregulation of similar biological processes (detoxification, neurotoxicity, modulation of cell signaling, embryonic development, reproduction, and tegument organization) by different mechanisms in metazoan parasites of fish. Since cuticle can act as a diffusion barrier for various anthelmintic compounds [ 17 ], combination of silver with conventional anthelmintic agents may allow better penetration of worm body. Silver nano-particles were shown to pass cell membranes and getting internalized in C. elegans by Meyer et al [ 18 ], and they proposed part of the toxicity observed to be mediated by ionic silver.…”
Section: Resultsmentioning
confidence: 99%
“…Pimentel-Acosta et al [14] also reported that silver nanoparticles at high and low concentrations activated dysregulation of similar biological processes (detoxi cation, neurotoxicity, modulation of cell signalling, embryonic development, reproduction, and tegument organization) by different mechanisms in metazoan parasites of sh. Since cuticle can act as a diffusion barrier for various anthelmintic compounds [15], combination of silver with conventional anthelmintic agents may allow better penetration of worm body. Silver nano-particles were shown to pass cell membranes and getting internalized in C. elegans by Meyer et al [16], and they proposed part of the toxicity observed to be mediated by ionic silver.…”
Section: Resultsmentioning
confidence: 99%